Computational based functional analysis of Bacillus phytases. (February 2016) - Verma, Anukriti; Singh, Vinay Kumar; Gaur, Smriti
Graphical abstract: Highlights: 13 Bacillus amyloliquefaciens sequences having phytase activity are analysed for their physicochemical characters and structural analysis. All 13 Bacillus amyloliquefaciens sequences found to be acidic and stable. These sequences are optimally effective in the pH range ubiquitous in the digestive tract of monogastric animals and thus are apt to be exploited as feed additives. Abstract: Phytase is an enzyme which catalyzes the total hydrolysis of phytate to less phosphorylated myo-inositol derivatives and inorganic phosphate and digests the undigestable phytate part present in seeds and grains and therefore provides digestible phosphorus, calcium and other mineral nutrients. Phytases are frequently added to the feed of monogastric animals so that bioavailability of phytic acid-bound phosphate increases, ultimately enhancing the nutritional value of diets. The Bacillus phytase is very suitable to be used in animal feed because of its optimum pH with excellent thermal stability. Present study is aimed to perform an in silico comparative characterization and functional analysis of phytases from Bacillus amyloliquefaciens to explore physico-chemical properties using various bio-computational tools. All proteins are acidic and thermostable and can be used as suitable candidates in the feed industry.